simplificando a expressão
![{ {2}^{9} \div ( {2}^{2} .2) {}^{3} \: {}^{2} } { {2}^{9} \div ( {2}^{2} .2) {}^{3} \: {}^{2} }](https://tex.z-dn.net/?f=%7B+%7B2%7D%5E%7B9%7D++%5Cdiv+%28+%7B2%7D%5E%7B2%7D+.2%29+%7B%7D%5E%7B3%7D+%5C%3A++%7B%7D%5E%7B2%7D++%7D)
Soluções para a tarefa
Respondido por
1
Resposta:
Explicaçãopasso a passo:
2^9 : [ (2^2 . 2)^3]^2
= 2^9 : [(2^3)^3]^2
= 2^9 : [2^9]^2
= 2^9: 2^18
= 2^(9-18)
= 2^(-9)
Explicaçãopasso a passo:
2^9 : [ (2^2 . 2)^3]^2
= 2^9 : [(2^3)^3]^2
= 2^9 : [2^9]^2
= 2^9: 2^18
= 2^(9-18)
= 2^(-9)
Perguntas interessantes
Pedagogia,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Pedagogia,
7 meses atrás
Biologia,
7 meses atrás
Matemática,
1 ano atrás
Espanhol,
1 ano atrás